FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI MASYARAKAT DALAM KEPEMILIKAN JAMBAN KELUARGA DI GANTING PARAK GADANG KECAMATAN PADANG TIMUR KOTA PADANG TAHUN 2019 - Yusfita, Ermi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Disposal of feces is one of the waste materials that brings many problems in the health sector such as the increased risk of infectious diseases. Provision of feces disposal facilities is closely related to the level of economy, education and knowledge. Based on the initial survey of 20 houses in Ganting Parak Gadang, 15 houses (75%) did not have latrines. The purpose of this study is to find out the Factors Associated with Community Participation with Family Latrine Ownership in Ganting Parak Gadang Padang Timur District, Padang City in 2019. From the results of the univariate analysis showed that most (78.4%) families did not have latrines and from the results of observations found 21 families had latrines that met the requirements. Most (57.5%) respondents stated that the role of health workers was not good as a result of bivariate analysis showed that there was a significant relationship between the economic level and latrine ownership (P Value = 0.026): OR = 4.579). Multivariate results show that the most related are the economic level and the role of officers (P value= 0.000). It is recommended to health workers in Ganting Parak Gadang health center in Padang Timur City, Padang City Extension to family heads who do not have family latrines to immediately build family latrines and will have an impact on health if they do not have latrines and provide counseling to the community so as to increase community awareness family toilet.Keywords: Latrine Procurement, Knowledge Level, Education, Economy.